Republic of India - eGovernance in the North East : Reducing Public Administration Constraints to Improve Service Delivery - World Bank (Washington, DC, 2014)
The Government of Assam (GoA) is engaged in a process of improving services to citizens. The focus on better services to citizens is in line with the National e-Government Plan (NeGP), with a number of existing and anticipated Union Acts, and with recently passed acts in Assam, especially the Assam Right to Public Services Act of 2012. The GoA is fully aware that progress on service delivery will require attention to both vertical and horizontal connectivity, and it intends to develop a Strategic Action Plan which focuses on these critical elements. The policy dialogue with the Government of Assam and review of relevant documents reveal general agreement on main public administration constraints (PAC's) to service delivery. The current report proposes a gradual reform approach, with a focus on searching for improvements that can be accomplished with a reasonable effort. The present report is structured as follows. Chapter two, 'Public Administration Constraints (PAC's)', provides a detailed diagnostic of constraints identified in Assam, groups those under five headings, and proposes actions to address each of the constraints. Chapter three, 'the way forward' proposes a process leading to the preparation and adoption by the Government of Assam of a strategic action plan to address to address selected PAC's.